Physician satisfaction with a critical care clinical information system using a multimethod evaluation of usability. (April 2018) - Hudson, Darren; Kushniruk, Andre; Borycki, Elizabeth; Zuege, Danny J.
Abstract: Introduction: Physician satisfaction with electronic medical records has often been poor. Usability has frequently been identified as a source for decreased satisfaction. While surveys can identify many issues, and are logistically easier to administer, they may miss issues identified using other methods This study sought to understand the level of physician satisfaction and usability issues associated with a critical care clinical information system (eCritical Alberta) implemented throughout the province of Alberta, Canada. Method: All critical care attending physicians using the system were invited to participate in an online survey. Questions included components of the User Acceptance of Information Technology and Usability Questionnaire as well as free text feedback on system components. Physicians were also invited to participate in a think aloud test using simulated scenarios. The transcribed think aloud text and questionnaire were subjected to textual analysis. Results: 82% of all eligible physicians completed the on-line survey (n = 61). Eight physicians were invited and seven completed the think aloud test. Overall satisfaction with the system was moderate. Usability was identified as a significant factor contributing to satisfaction. The major usability factors identified were system response time and layout. The think aloud component identified additional factors beyond those identified in the on-line survey. Conclusion: This study found a modestly high level of physician satisfaction with a province-wide clinical critical care information system. Usability continues to be a significant factor in physician satisfaction. Using multiple methods of evaluation can capture the benefits of a large sample size and deeper understanding of the issues.